The relationship between cues to action towards food safety behavior among food program students at vocational school - Piee @ Shafiee, Nor Faradillah; Abu, Rosini; Mat Rashid, Abdullah (IDOSI Publications, 2014)
This paper aims to identify the level of cues to action and level of food safety behavior among food program students at Vocational School in Malaysia. Furthermore, this paper aims to recognize the relationship between cues to action and food safety behavior among students. Cues to action were measured by identifying factors such as media, communication with others and caution label in food packaging that affect students to change their behavior. Aspects in food safety behavior that have been measured were personal hygiene, food handling and food borne illness prevention. The respondents of this research were 266 food program students at Vocational School in Malaysia. Sampling method used was based on stratified random sampling and simple random sampling. The data were gathered and analyzed using descriptive and inferential statistics such as Pearson R correlations. Results show that there was a significant relationship between cues to action and food safety behavior.